Discerning Good from Bad Credit Booms : The Role of Construction - Dell'Ariccia, Giovanni (Staff Discussion Notes; Staff Discussion Notes ;, 2020)
Credit booms are a focal point for policymakers and scholars of financial crises. Yet our understanding of how the real sector behaves during booms, and why some booms may go bad, is limited. Despite a large and growing body of literature, most of the work has focused on aggregate economic activity, and relatively little is known about which industries benefit and which suffer during these episodes. This note aims to fill this gap by analyzing disaggregated output and employment data in a large sample of advanced and emerging market economies between 1970 and 2014.